1987
DOI: 10.1136/adc.62.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal swellings in the under 5s.

Abstract: SUMMARY Scrotal swelling is a common cause of referral to the paediatric surgical services in Edinburgh, constituting 12% of total admissions. Of these, 2818 (65%) were in boys under the age of 5 years, with a wide variety, including inguinal hernias, hydroceles, testicular torsion, tumours, and some interesting but uncommon conditions. A retrospective study was performed over a 12 year period to assess the incidence, aetiology, mode of presentation, disease, and management of scrotal swellings in boys under 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Based on open processus vaginalis, indirect IH is known as the most common indication for surgery in the first months of life [ 18 , 19 ]. While the incidence of IH in full-term neonates was estimated 1–5% [ 20 22 ], the first study of hernias in BA patients demonstrated an increased incidence of IH (8.1%) [ 11 ], which is corroborated by our findings revealing even a higher incidence of IH (19.6% in our BA patients). Therefore, we could confirm that BA patients suffer from a high risk for the development of IH.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on open processus vaginalis, indirect IH is known as the most common indication for surgery in the first months of life [ 18 , 19 ]. While the incidence of IH in full-term neonates was estimated 1–5% [ 20 22 ], the first study of hernias in BA patients demonstrated an increased incidence of IH (8.1%) [ 11 ], which is corroborated by our findings revealing even a higher incidence of IH (19.6% in our BA patients). Therefore, we could confirm that BA patients suffer from a high risk for the development of IH.…”
Section: Discussionsupporting
confidence: 88%
“…Male gender is a well-recognized risk factor for IH development in healthy children [ 19 ]. While Wilson-Storey described an overall boy : girl ratio of 4 : 1, Powell et al found a more than 9-fold increased relative risk for IH in boys compared to female neonates [ 18 , 22 ]. In BA patients, Zani and Davenport observed a higher proportion of boys in hernia patients compared to nonhernia patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this is the rare occurrence of acute scrotum in neonates and young infants [6,7]. As hydrocele and inguinal hernia account for most acute or chronic scrotal swelling [8], it is not difficult for physicians to recognize hydrocele and inguinal hernia. Instead, it is confusing and difficult for physicians to diagnose acute scrotum resulting from other causes, such as TT and epididymo-orchitis (EO) in neonates and young infants.…”
Section: Index Wordsmentioning
confidence: 99%
“…The most common diagnoses at surgery for acute scrotal symptoms, often referred to as "acute scrotum," in the first year of life are testicular torsion and torsion of the testicular or epididymal 178 http://dx.doi.org/10.1053/j.sult.2015.01.008 appendages. [9][10][11] The remainder of the differential diagnoses for "acute scrotum" in this age group include hematocele, scrotal hematoma, meconium peritonitis, meconium pseudocyst, idiopathic scrotal edema, orchitis, epididymitis, and abscess. Additional palpable abnormalities include benign and malignant lesions, as well as splenic or adrenal rests.…”
Section: Testicular Pathology In the Newborn And Infantmentioning
confidence: 99%